silver fox (1975)
silver n On Niger Sound we saw a good silver fox. PRINTED ITEM DNE-cit G.M.Story 9/75 JH 9/75 Used I and Sup Used I and Sup 2 Used I ~ fir/fox/hair (fox)/jar/thaw/ patch fox, GLITTER, PATCH FOX.